Making True Amplitude Angle Domain Common Image Gathers Using Invertible Radon Transform (Communications in Computational Physics, 2020)
Converting subsurface offset domain common image gathers (ODCIGs) toangle domain common image gathers (ADCIGs) through a Radon Transform (RT) ineither the spatial or wavenumber domain is efficient and valid except for the distortion of both frequency spectrum and amplitude versus angle (AVA) effect. This paperpresents two modifications to the existing method to keep the frequency spectrum ofthe resultant ADCIGs the same as the input data and to preserve the relative amplitudes. The spectrum invariance is achieved by replacing the conventional RT or slantslack by an invertible RT. Amplitude preservation is obtained by applying an amplitude correction factor in the angle domain. Tests on both synthetic and field datasetsvalidate the accuracy of these modifications.
Keywords: True amplitude; ADCIG; reverse time migration; invertible Radon transform.